Break-induced loss of heterozygosity in fission yeast: dual roles for homologous recombination in promoting translocations and preventing de novo telomere addition. - Cullen, J; Hussey, S; Walker, C; Prudden, J; Wee, B; Davé, A; Findlay, J; Savory, A; Humphrey, T (2007)
Loss of heterozygosity (LOH), a causal event in tumorigenesis, frequently encompasses multiple genetic loci and whole chromosome arms. However, the mechanisms leading to such extensive LOH are poorly understood. We investigated the mechanisms of DNA double-strand break (DSB)-induced extensive LOH by screening for auxotrophic marker loss approximately 25 kb distal to an HO endonuclease break site within a nonessential minichromosome in Schizosaccharomyces pombe. Extensive break-induced LOH was infrequent, resulting from large translocations through both allelic crossovers and break-induced replication. These events required the homologous recombination (HR) genes rad32(+), rad50(+), nbs1(+), rhp51(+), rad22(+), rhp55(+), rhp54(+), and mus81(+). Surprisingly, LOH was still observed in HR mutants, which resulted predominantly from de novo telomere addition at the break site. De novo telomere addition was most frequently observed in rad22Delta and rhp55Delta backgrounds, which disrupt HR following end resection. Further, levels of de novo telomere addition, while increased in ku70Delta rhp55Delta strains, were reduced in exo1Delta rhp55Delta and an rhp55Delta strain overexpressing rhp51. These findings support a model in which HR prevents de novo telomere addition at DSBs by competing for resected ends. Together, these results suggest that the mechanisms of break-induced LOH may be predicted from the functional status of the HR machinery.